Strong Convergence of an Implicit Iteration Algorithm for a Finite Family of Pseudocontractive Mappings - Yeong-Cheng Liou (Journal of Inequalities and Applications, 2008)
Strong convergence theorems for approximation of common fixed points of a finite family of pseudocontractive mappings are proven in Banach spaces using an implicit iteration scheme. The results presented in this paper improve and extend the corresponding results of Osilike, Xu and Ori, Chidume and Shahzad, and others.